Balancing Livestock Production and Wildlife Conservation in and around Southern Africa's Transfrontier Conservation Areas. Issue 6 (22nd October 2013) - Thomson, G. R.; Penrith, M. ‐L.; Atkinson, M. W.; Atkinson, S. J.; Cassidy, D.; Osofsky, S. A.
Summary: Biodiversity conservation, of which the transfrontier conservation area movement is an integral part, and more effective livestock production/trade are pivotal to future rural development in southern Africa. For that reason, it is imperative to effectively ameliorate the obstacles that have impeded progress towards the coexistence of these two sectors for more than half a century. Transboundary animal diseases, foot and mouth disease in particular, have been and continue to be the most important of these obstacles. Fortunately, new developments in international sanitary standards applicable to trade in commodities and products derived from animals are beginning to make a solution possible. However, while progress in principle has been achieved, practical implementation remains problematic for technical reasons, exacerbated by inconsistent attitudes towards acceptance of non‐traditional international trade standards. This paper describes the background to this situation, progress that has been achieved in the recent past and remaining difficulties that need to be overcome to advance towards achievement of balanced rural development in southern Africa.